Penggunaan Dosis Dekomposer dan Perbedaan Waktu Inkubasi Pada Bokashi Kotoran Walet Terhadap Pertumbuhan dan Hasil Tanaman Sawi Hijau (Brassica Juncea L.) di Tanah Marginal - Musahidin Musahidin; Sulistyo Sidik Purnomo; Vera Oktavia Subardja; Fawzy Muhammad B (Peneliti.net, 2022)
The addition of organic matter in marginal soils is important to do in an effort to increase soil fertility so that plants can grow and produce optimal production. The purpose of this study was to obtain a dose of decomposer and length of incubation time in bokashi swallow droppings capable of increasing the growth and yield of green mustard plants (Brassica juncea L.) in marginal soils. This research was conducted at a screenhouse located in Sentiong Village, Rawagempol Wetan Village, Cilamaya Wetan Subdistrict, Karawang Regency, West Java. The method used was an experimental method with a factorial Randomized Block Design (RBD) consisting of two factors. The first factor is the decoposer dose consisting of 2 levels, namely: D1 (0 ml) and D2 (10 ml). The second factor is the length of incubation time consisting of 5 factors: W1 (0 days), W2 (4 days), W3 (8 days), W4 (12 days), and W5 (16 days). The results showed that there was no noticeable influence on the use of decoposer doses and differences in incubation time in bokashi swallow droppings against plant height parameters, number of leaves, fresh weight of plants, and dry weight of plants. However, there is an interaction influence on the parameters of the greenish level of the leaves. Giving of decomposer 10 ml (D2) treatment with an incubation time of 12 days (W4) was the best combination of treatment because it is able to provide the highest values on the height parameters of the plant (D2: 3,83-26,44 cm) and (W4: 3,88-26,67 cm), the number of leaves (D2: 3,87-11,00 leaf strands) and (W4: 3,89-11,11 leaf strands), and fresh weight of the plant (D2: 93,60 grams) and (W4: 102,18 grams).